The Land, the Bible, and History : Toward the Land That I Will Show You - Marchadour, Alain, 1937- (Book collections on Project MUSE., 2007)
This unique book offers a Catholic view of the Holy Land in the debate that rages among Jews, Christians, and Muslims. Alain Marchadour and David Neuhaus, two biblical scholars and priests living in Jerusalem, clearly analyze the Promised Land--as concept, history, and contested terrain--in Catholic teaching and doctrine. They offer an analytical reading of the entire Christian Bible (Old and New Testaments) with reference to the idea of the Land promised by God. They explore early and medieval attitudes, especially with regard to the Holy Places and the Jewish people. Moving carefully to the present day, they focus on anti-Semitism, the tragedy of the Shoah, Western colonialism in the Middle East, the creation of the State of Israel, and the birth of the Palestinian refugee problem as they examine Catholic reactions to the tumultuous events of the nineteenth and twentieth centuries, particularly the renewal of Catholic thought in the aftermath of the Second Vatican Council.